Análise comparativa da eficiência de três raspadores ósseos com diferentes aberturas da área coletora - Campos, Camilla Neves (2009)
Autogenous bone grafts present better results in dental implants regeneration procedures and normally are used as blocks or particles forms. The autogenous graft obtainment technique with bone scrapers makes possible the collection with less invasiveness. The objective of this study was making a comparative analysis of three bone scrapers with different apertures collective area. An efficacy analyses was done by an in vitro test with 27 Neodent® bone scrapers divided in 03 groups: group 1- represented by the commercially available scrapers.; groups 2 and 3- constituted by the same scrapers modified with a respective 1 or 2 mm magnification in each collective area The devices were randomicaly used in a double-blind study. The scraping was done in a 6 cm segment of a bovine femur by performing 20 strokes in 10 sessions. The results were submitted to Kruskal-Wallis test. The average weight of bone collected were: group 1- 0.115g ± 0.06, group 2- 0.129g ± 0.07 and group 3- 0.084g ± 0.04 (p=0.758). Despite the increase of 2 mm in the apertures of the storage chamber had resulted in excessive loss of material during the scraping, and the increase of 1 mm have favored the harvesting of more bone quantity, the differences were not statistically significant.